KHARAKTERISASI ENZIM KASAR GLUKOAMILASE DARI Saccharomycopsis sp. - Naiola, Elidar (BERITA BIOLOGI, 2006)
Saccharomycopsis sp. produced glucoamylase (a-1,4 glucanglucohydrolase; EC 3.2.1.3) shown by the presence of clear zone on media containing 0.2% yeast extract, 0.5% pepton, 0.3% KH2PO4, 0.05% MgSO4. 7H2O, 0.01% CaClr2H2O, 2% agar and 2% soluble starch. In liquid media containing soluble starch glucoamylase production reached a maximum at 2 days fermentation, with levels of 4.2 x 10 U/ml (one unit activity is define as micromoles of glucose produce per ml per minute).Studies on the glucoamylase characterization revealed that the optimum temperature for activity was 40°C - 50°C. The enzyme was stable for lh at 45"C - 55°C, while at 60°C to 65°C, 40% of the original activities were lost. The optimum pH of the enzyme was 6.0. After incubation of crude enzyme solution for 1 h at pH 8.0, a decrease of about 40% of its original activity was observed. Saccharomycopsis sp. produced high glucoamylase when it was grown in media containing rice flour as carbon source with the glucoamylase activity at 9,28 x 10 U/ml.